(untitled) ("Temas Sociais" Journal, 2024)
For many women, immigration is a highly positive experience from the point of view of empowerment and individual emancipation. However, for others, the experience entails particular vulnerability and exposure to situations of poverty, discrimination and exploitation. The problems inherent in managing family and professional life affect almost all women, but not all equally, and are more severe for those who live in an immigrant context and have many dependent children. The aim of this study - in which the object of study is Cape Verdean women living in Bairro São Marçal, in Portela de Carnaxide, in the municipality of Oeiras - is to identify the strategies used by these women to reconcile family and professional life and, by understanding their characteristics, to deepen our knowledge of their life paths, work, cultural habits and the level of qualification of the household: the qualitative study sampled 26 interviewees, all Cape Verdean women. As a result, it was observed that in many families, there tends to be a relinquishing of parental responsibilities by men, especially after separation or divorce. In addition, there is little sharing and alternation of roles. In addition to these consequences, which are perceived as worrying problems, a growing number of young people in the neighborhood who are absent from school and/or drop out, and who even display deviant or delinquent behavior.